The Influence of Fiction Versus Nonfiction on Political Attitudes (Communication research reports, 2015)
An experiment was conducted to test the influence of fictional versus real events portrayed in videos (defined by the fiction versus nonfiction labels of the videos) on political attitudes. It found that the labels interacted with individual differences in need for cognition (NC) to influence participants' support for social welfare programs such that introducing the videos as fictional films versus documentaries produced more support among low-NC participants but had little impact among high-NC participants. The interaction effect was explained by the extent to which participants argued against the videos. The findings not only shed light on the relative persuasiveness of fictional and nonfictional media messages but also suggest how people may process these messages.
https://katalog.adlr.link/Record/ai-68-OLC1959978543